Millenium Development Goals (Mdgs) and Sustainable Development Goals (Sdgs) in Social Welfare - Gwilim Diouf (GoAcademica Research & Publishing, 2019)
Sustainable Development Goals (SDGs) are designed as the successor of the Millennium Development Goals (MDGs) as the MDGs’ goals have not been achieved by the end of 2015. The SDGs is an action plan for the humankind, the planet, and the prosperity that also aims to strengthen universal peace in a broad freedom. It exists to overcome extreme poverty as the greatest global challenge. The SDGs concept is needed as a new development framework that accommodates all the changes occur after the 2015-MDGs, especially related to the world's changes since 2000 regarding the issue of deflation of natural resources, environmental degradation, crucial climate change, social protection, food and energy security, and a more pro-poor development. MDGs aimed only for the developing countries, while SDGs have a more universal goal. The SDGs is present to replace the MDGs with better goals to face the world future challenge. It has 17 goals and 169 targets that will stimulate actions for the next 15 years, focusing on the significant areas for the humanity and the planet, i.e., the people, planet, prosperity, peace, and partnership.